PERANCANGAN DAN IMPLEMENTASI PENGGUNAAN BARCODE READER PADA SISTEM APLIKASI PEMBAYARAN SPP BERBASIS WEB - Zaenal Mustofa; Toni Wijanarko Adi Putra (Jurnal Publikasi Teknik Informatika, 2022)
Along with the rapid development of technology, especially in the field of information technology, it demands almost every part of our lives to take advantage of it. Especially in daily work that demands a fast, precise and accurate process. Therefore, at this time information technology cannot be separated from part of our daily work processes. To get fast work results, it needs to be supported by simple and applicable tools. Madrasah Tsanawiyah (MTs) Jepara is a junior secondary level formal education institution which is geographically located in Karangawen Village, Karangawen District, Demak Regency, with a total of about 800 students divided into 25 classes. To serve student payments with a large number of students, MTs Jepara is no longer serving manually, namely by writing in a book to record payment transactions, but has used a student financial payment application created using Microsoft Access. With this application, all student financial payment transactions can be accessed easily and quickly which are served by Administrative Staff to support the work process. The purpose of this research is to build a school financial payment system with barcode tools at MTs Jepara Demak to help speed up data input on the student financial payment application at MTs Jepara Demak so that services in student financial payments at MTs Jepara Demak become faster. In this study, the application used is Microsoft Access programming using Barcode Reader as a tool